2017
DOI: 10.15406/oajs.2017.01.00014
|View full text |Cite
|
Sign up to set email alerts
|

Using of Citrus By-products in Farm Animals Feeding

Abstract: Conventional feedstuffs are often expensive and therefore the utilization of agroindustrial by-products as feedstuffs may be economically worthwhile. Ruminant feeding systems based on locally available by-product feedstuffs (BPF) are often a practical alternative because the rumen microbial ecosystem can utilize BPF which often contain high levels of structural fiber to meet their nutrient requirements for maintenance, growth, reproduction and production. Citrus by-product includes numerous BPF which varies ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 18 publications
(26 reference statements)
9
30
1
Order By: Relevance
“…Nutrition accounts for 70% of the total cost of rabbit or animal production (Oyawoye and Nelson, 1999;Spring, 2013). Incorporation of fruits and vegetable wastes in animal feeds improved palatability of diet and consequently increased the feed intake in addition to decrease feed cost (Chaudry et al, 2004 andAlnaimy et al, 2017). Sun dried orange peel meal and citrus pulp has been used as untraditional calorie and protein source in broiler diets (Oluremi et al, 2006;De Bals et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nutrition accounts for 70% of the total cost of rabbit or animal production (Oyawoye and Nelson, 1999;Spring, 2013). Incorporation of fruits and vegetable wastes in animal feeds improved palatability of diet and consequently increased the feed intake in addition to decrease feed cost (Chaudry et al, 2004 andAlnaimy et al, 2017). Sun dried orange peel meal and citrus pulp has been used as untraditional calorie and protein source in broiler diets (Oluremi et al, 2006;De Bals et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…e rumen microbes of ruminants can convert the fibres into useful nutrients. Studies have shown that inclusions of some of the residues/wastes (apple, banana, cabbage, chicory, citrus, grape, mango, peas, pineapple, and pumpkin) in poultry and livestock rations have significantly improved the animals' general well-being and reproductive traits [16][17][18][19][20][21][22][23].…”
Section: Selected Agricultural Residues In Livestock Nutritive Diet Omentioning
confidence: 99%
“…In addition to the beneficial fibre content, fermentable carbohydrates contained in the pulp of the Citrus fruit provide a source of energy to ruminal microbes. However, soluble carbohydrates and acid detergent fibres equally play a vital role in providing ruminal microorganisms with energy required for the digestive system [23].…”
Section: Nutritious Dietary Resources Derived From Citrus Pulpmentioning
confidence: 99%
“…In general, the citrus pulp residue that industries produce is transformed into silage. Silage is commonly used as a raw material in cattle and sheep nutrition with good results in terms of milk production (Piquer et al 2009) and animal growth (Alnaimy et al 2017). In the last few decades, the use of silage has extended to nutrition for monogastric animals, such as pigs (Amorim et al 2011(Amorim et al , 2014Crosswhite et al 2013;Watanabe et al 2009Watanabe et al , 2010 and chickens (Mourão et al 2008;Silva et al 2013), with no adverse growth parameters.…”
Section: Introductionmentioning
confidence: 99%